Mini-Open Femoroacetabular Osteoplasty: Risk Factors for Failure and Conversion to Hip Arthroplasty. (17th June 2020) - Ceylan, Hasan Huseyin; Vahedi, Hamed; Azboy, Ibrahim; Aali Rezaie, Arash; Parvizi, Javad
Abstract : Background: Surgical treatment of femoroacetabular impingement (FAI) has been increasing over the past decade with reports of favorable results in alleviating patient symptoms. However, progression of osteoarthritis in these patients may necessitate total hip arthroplasty (THA) for the treatment of unresolved or recurrent hip pain and accompanying disability. Identifying the risk factors for disease progression and treatment failure can help orthopaedic surgeons to select the appropriate patients for joint-preservation procedures and allow more informative discussions. Methods: With use of the prospective database of hip-preservation surgery at our institution, 652 patients (324 men and 328 women) with FAI who had undergone femoroacetabular osteoplasty (FAO) between December 2004 and April 2016 were identified. Treatment failure was defined as the need for THA. At the latest follow-up, 68 (9.08%)of 749 hips had undergone THA because of the recurrence of symptoms and the development of osteoarthritis. The groups of patients who had or had not undergone conversion to THA were compared with respect to age, sex, body mass index (BMI), surgeon experience, duration of preoperative symptoms, preoperative and postoperative alpha angles, radiographic parameters of hip dysplasia, a perioperative chondral lesion, labral abnormalities and interventions, acetabular retroversion, and severity of osteoarthritis (Tönnis grade). Results: The mean age (and standard deviation) at the time of the index FAO was 41.9 ± 10.5 years for patients who had had a failure of FAO, compared with 33.4 ± 11.1 years for those who had not. Risk factors for treatment failure included a longer mean symptomatic period before the FAO procedure, older age, higher mean BMI, the presence of hip dysplasia, acetabular retroversion, higher preoperative alpha angle, a full-thickness acetabular chondral lesion, Tönnis grade-1 and 2 osteoarthritis, labral hypertrophy, and total labral resection during FAO. The rate of failure was related to the experience of the surgeon, with fewer failures occurring in the later years of surgery as compared with the earlier years. Conclusions: The present study identified a number of variables that influence the outcome of FAO. Surgeons performing hip-preservation procedures should be aware of these risk factors for failure, and a more cautious approach is recommended for patients with these risk factors. Level of Evidence: Prognostic Level IV . See Instructions for Authors for a complete description of levels of evidence.